Robust Canonical Correlation Analysis on Leakage Current Behaviors of Geothermal Polluted Porcelain Insulators - Waluyo, Waluyo; Sinisuka, Ngapuli Irmea; Suwarno, Suwarno (Semesta Teknika, 2009)
This study presents the leakage current measurements results of three natural geothermal polluted porcelain insulators. The insulators consisted of one new-clean insulator, as reference, and three polluted insulators. The carried out measurements were leakage current and applied high voltage waveforms, used a two-channel storage digital oscilloscope, in a hermetically sealed chamber, where temperature, humidity, pressure and applied voltage amplitude could be adjusted and measured simultaneously. The leakage current waveforms were analyzed using the FFT and the statistical concerns were analyzed by the Fast-Minimum Covariance Determinant (FMCD) of robust multivariate statistical tools, and canonical correlation analysis (CCA). The result indicated that after the fundament, the second highest of harmonics leakage current were fifth harmonics. The leakage current waveforms were significantly influenced by humidity, besides pollution. The dependent or output variables are linear functions of independent or input variables. Based on CCA, the dependent parameters depended on input parameters tightly, with the canonical correlations were more than 0.99. The leakage currentÂ  amplitudes were still predominantly influenced by applied voltage amplitudes, where the phase angles and THD were slightly influenced by relative humidity. On these experimental measurements, the insulators were still in normal operation.Â